Numerical Analysis of the Influence of Foundation Pit Blasting on a Nearby Metro Tunnel - Haibo Wang; Yaoyao Wang; Mengxiang Wang; Qi Zong (Shock and Vibration)
It is important to guarantee the safety of adjacent underground structures during the foundation pit blasting excavation of modern city construction. The blasting excavation construction of a large, deep foundation pit near an existing metro station of Guangzhou Metro Line 3 is used as the example in this study. Based on blasting vibration field test results, the influence of blasting dynamic load on the lining of an adjacent metro tunnel is numerically analyzed in simulation using Fast Lagrangian Analysis of Continua 3D (FLAC3D), and the relationships between the blasting vibration velocity and stress and the displacement of the metro tunnel lining are obtained. The results show that the stress of lining structure is within the allowable range under the experimental blasting conditions, the lining displacement increases linearly with the applied dynamic vibration velocity, and the vertical displacement of the lining is more obviously affected than the horizontal displacement by the dynamic load. This study can be used as a basis for the control of blasting vibration in a complex urban environment. Its practical application shows that the proposed blasting plan and parameters are reasonable and effective.